Christians and Pagans. Distribution of Power in the Senate of Rome in the Late 4th Century - Piechocka-Kłos, Maria (Studia Warmińskie, 2013)
In the minds of people who lived in the late Roman Empire, society was a structure in which power and influence were determined by one’s position in the social hierarchy. Therefore, to be elected senator in the ancient world was highly ennobling – something worth great efforts to achieve. Moreover, the end of the 4th century was a time of coexistence and intertwining (also in the senate) of pagan and Christian influence. This paper presents the distribution of power and pagan and Christian influence in the Roman Curia in late antiquity, mainly during the reign of Valentinian II and Theodosius II, based on the Letter 72 [17] written by Ambrose, a hexametric poem Against Symmachus by Prudentius and Historia Nova by Zosimus. Scant information on the subject can be found only in a few fragments of these documents. Without doubt, an objective analysis of the issue is difficult because the ancient sources which deal with it cannot be regarded as sufficient.